The Effects of Manganese Dopant Content and Calcination Temperature on Properties of Titania-Zirconia Composite - Muhamad Imam Muslim; Rian Kurniawan; Mokhammad Fajar Pradipta; Wega Trisunaryanti; Akhmad Syoufian (Indonesian Journal of Chemistry, 2021)
The effects of dopant content and calcination temperature on Mn-doped TiO2-ZrO2 structure and properties were successfully investigated. Composite of Mn-doped titania-zirconia was synthesized by sol-gel method. Titanium(IV) isopropoxide was used as the precursor of TiO2, while zirconiapowder was used as another semiconductor. MnCl2∙4H2O was used as the source of dopant in this study. Various amounts of manganese were incorporated into TiO2-ZrO2 and calcination was performed at temperatures of 500, 700 and 900 °C. Synthesized composites were characterized by Fourier-transform infrared spectroscopy (FTIR), specular reflectance UV-Vis spectroscopy (SR UV-Vis), X-ray diffraction method (XRD) and scanning electron microscopy equipped with X-ray energy dispersive spectroscopy (SEM-EDX). The results showed that Mn-doped TiO2-ZrO2 with the lowest bandgap (2.78 eV) was achieved with 5% of Mn dopant and calcined at 900 °C, while Mn-doped TiO2-ZrO2 with the highest bandgap (3.12 eV) was achieved with 1% of Mn dopant content calcined at 500 °C.